Anaplasma marginale in goats from a multispecies grazing system in northeastern Brazil - Barbosa, Iago C.; André, Marcos R. [UNESP]; Amaral, Renan Bressianini do [UNESP]; Valente, Jessica D.M.; Vasconcelos, Priscylla C.; Oliveira, Celso J.B.; Jusi, Marcia Mariza Gomes; Machado, Rosangela Z. [UNESP]; Vieira, Thállitha S.W.J.; Ueti, Massaro W.; Vieira, Rafael F.C. (Elsevier, 2021)
Anaplasma marginale, a tick-borne α-proteobacterium that causes significant economic losses for the cattle industry worldwide, has been increasingly detected in other animal species. This agent has been previously detected in buffaloes and goats co-grazed with cattle in Brazil. This study aimed to investigate the occurrence of A. marginale in a multispecies (goats, sheep and cattle) grazing farm in the State of Paraíba, northeastern Brazil. A total of 119 goats, 71 sheep, and five cattle were evaluated. An epidemiological questionnaire was applied to the farm owner addressing age, gender, and presence of ticks. Serum samples from goat, sheep and cattle were tested for anti-Anaplasma marginale antibodies by a commercial MSP5-based on indirect enzyme-linked immunosorbent assay (iELISA). EDTA-blood samples were screened for A. marginale- and A. ovis-infection by PCR using primers targeting Anaplasma spp. msp4 gene. Sequencing of the repeat region of the msp1α gene was used for genotyping A. marginale strains found in the present study. A total of 47/119 (39.5 %, 95 % CI: 31.1–48.4 %) goats and 2/71 (3%, 95 % CI: 0.7–9.7 %) sheep were seroreactive for A. marginale rMSP5 by the commercial iELISA. All cattle were seronegative for A. marginale. Anaplasma spp. msp4 PCR results revealed that two out of 119 (1.7 %; 95 % CI: 0.4–5.9 %) goats tested positive and all sheep and cattle samples were negative. It was not possible to sequence one sample. Therefore, the other sequencing sample found tandem repeats of A. marginale msp1α gene demonstrating that goat was infected with the genotype F/91. Rhipicephalus microplus ticks were found parasitizing goats but not on sheep or cattle. Considering that in Brazil A. marginale genotype F/91 and the MSP1a tandem repeat F has only been detected in goats so far, we hypothesized that this genotype may be related to goats.
Keywords: Anaplasmosis; Cattle; Goat; msp1α and msp4; Rhipicephalus microplus